Perkembangan Prinsip Tanggung Jawab (Bases Of Liability) dalam Hukum Internasional dan Implikasinya terhadap Kegiatan Keruangangkasaan - Neni Ruhaeni (Jurnal Hukum IUS QUIA IUSTUM, 2014)
This research discusses the development of bases of liability in international laws and its implications to any outer space activities. The research method was normative-juridical. The findings show that: first, based on the development history, there are three bases of liability in international laws; each has its own characters and implementation mechanisms. Second, the important implications of the development of bases of liability in international laws of outer space activities are written in Article II and Article III Liability Convention 1972 which are the elaboration of the stipulations in Article VII of the Outer Space Treaty 1967. As a consequence of Indonesian’s participation in international outer space laws, bases of liability which is mentioned in Article II and Article III Liability Convention 1972 should be implemented in national legislation related to the liability in any outer space actitivies in Indonesia.